Homogeneous visible light-driven hydrogen evolution by the molecular molybdenum sulfide model [Mo2S12]2−. Issue 1 (7th November 2018) - Rajagopal, Ashwene; Venter, Felix; Jacob, Timo; Petermann, Lydia; Rau, Sven; Tschierlei, Stefanie; Streb, Carsten
Abstract : The first example of light driven, homogeneous hydrogen evolution reactivity by the smallest thiomolybdate cluster [Mo2 S12 ] 2− is reported together with initial insights into the catalytic and deactivation mechanism. Abstract : The visible light-driven hydrogen evolution reaction by the molecular molybdenum sulfide anion [Mo2 S12 ] 2− is reported. When coupled with the photosensitizer [Ru(bpy)3 ] 2+ (bpy = 2, 2′-bipyridine) and the electron/proton donor ascorbic acid, turnover numbers > 1600 and turnover frequencies > 700 h −1 are observed. Comparison with the prototype HER catalyst [Mo3 S13 ] 2− shows remarkable reactivity differences which are explored by initial mechanistic studies under reaction conditions.